THE INFLUENCE OF DIGITAL LITERACY AND RELATIONSHIP BUILDING ABILITY ON STUDENTS' ENTREPRENEURIAL DECISIONS WITH ENTREPRENEURIAL MOTIVATION AS A MEDIATING VARIABLE: A STUDY ON STUDENTS OF THE ENTREPRENEURSHIP STUDY PROGRAM - Suarni; Muhammad Rakib; Mahmuddin (Widya Balina, 2026)
Entrepreneurship Study Programme students at Universitas Negeri Makassar's Faculty of Economics and Business had their digital literacy and relationship-building skills examined to see how they affected their entrepreneurial decision-making. Additionally, it determines if entrepreneurial drive is a factor in the relationship between these variables. Data for the study is collected quantitatively via questionnaires. The 427 students who completed the programme between 2019 and 2024 are the ones included in the study. With a 5% margin of error, 207 students were selected by proportional random sampling using the Slovin algorithm. A Google Form questionnaire was used to gather the data. After that, SmartPLS version 4 was used to analyse the data using the PLS-SEM approach. According to the findings, digital literacy significantly impacts entrepreneurial decision-making for the better. Entrepreneurial decision-making is positively and significantly impacted by the capacity to develop connections. There was a positive and statistically significant association between digital literacy and the capacity to form relationships, which in turn influenced entrepreneurial drive. There was a positive and statistically significant relationship between entrepreneurial motivation and entrepreneurial decision-making. Students' entrepreneurial decision-making is influenced by their entrepreneurial drive, which in turn is influenced by their digital literacy and relationship-building abilities.